2017
DOI: 10.1080/10942912.2017.1297953
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of DNA extraction methods from fresh and processed yellowfin tuna muscle tissue

Abstract: The most common techniques used to identify tuna species include methods based on the detection of specific DNA. The quality of species-specific DNA crucially affects the efficiency of amplification during the subsequent polymerase chain reaction (PCR). Detection of DNA in processed products can be adversely affected by DNA fragmentation during the processing steps and the use of ingredients that may inhibit the PCR reaction. In this study, several processing treatments applied to the muscle tissue of yellowfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
2
24
0
2
Order By: Relevance
“…The DNA was considered to be satisfactorily pure when the ratios of the A260 to A280 were within the range of 1.7-2.0. DNA contamination with proteins usually reduces the A260 to A280 ratio to values lower than 1.7 (Cawthorn et al 2011;Piskata et al 2017). DNA is very sensitive to acid and alkaline agents, because of the mechanism of hydrolytic degradation of DNA (Peano et al 2004;Chapela et al 2007), and low pH media have been described as favouring a higher DNA degradation (Bauer et al 2003;Chapela et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA was considered to be satisfactorily pure when the ratios of the A260 to A280 were within the range of 1.7-2.0. DNA contamination with proteins usually reduces the A260 to A280 ratio to values lower than 1.7 (Cawthorn et al 2011;Piskata et al 2017). DNA is very sensitive to acid and alkaline agents, because of the mechanism of hydrolytic degradation of DNA (Peano et al 2004;Chapela et al 2007), and low pH media have been described as favouring a higher DNA degradation (Bauer et al 2003;Chapela et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DNA is largely unaffected by tissue source or sample damage [4,5]. However, fragment size is a limiting factor for the subsequent PCR [6]. Thus, DNA-based analytical methods represent a crucial approach for species identification in raw and highly processed meat products due to their high thermal stability and their very low detection limits.…”
Section: Introductionmentioning
confidence: 99%
“…which considerably influence the quality of DNA [19,20,21,22], it is necessary to individually optimize DNA isolation procedures for each type of food product. In addition, the chemical compounds present in food matrices (polysaccharides, proteins, collagen, polyphenols, fulvic acids, or lipids) may not be completely removed during the DNA extraction protocol and can affect the integrity of DNA or cause inhibition of subsequent PCR analysis [6]. Inhibitor compounds can interfere with PCR by decreasing or even completely inhibiting the activity of DNA polymerase [23].…”
Section: Introductionmentioning
confidence: 99%
“…DNA concentration is also affected by the ingredients of the mixtures contained in the product. The additions of polysaccharides, proteins, or lipids and other ingredients in processed products cause the isolated DNA mix with contaminant compounds (Piskata et al 2017). Maulid and Nurilmala (2015) reported that the processed mackerel cracker DNA product could not be observed on agarose gel electrophoresis due to low concentration.…”
Section: Dna Concentration and Puritymentioning
confidence: 99%